Hubungan antara Red Blood Cell Count (RBC) dan Retinopati Diabetik pada Pasien Diabetes Melitus tipe 2 - Irmayani Irmayani; Santi Syafril; Dharma Lindarto (Fakultas Kedokteran USU, 2016)
Background : Diabetic retinopathy is main complications of diabetes. Some studies suggest a relation between red blood cell count (RBC) and diabetic retinopathy. Diabetic retinopathy is diagnosed with funduscopic examination, while red blood cell count can be seen from the peripheral blood examination, with the result is a relation of a decreased red blood cell count with diabetic retinopathy.Objective : To determine the relation between RBC count and diabetic retinopathy in diabetic type 2 patients. So that these parameters can be used as prospective and reliable indicators to detect complication of diabetes mellitus in the target organs, specially the eyes as early as possible.Methods: This cross sectional study with measurement data from March - June 2015, there were 49 patients with type 2 diabetic examined from the anamnesis, examination of vital signs, physical examination, and examination of routin peripheral blood, HbA1C ,fasting and 2 hours post prandial glucose count, lipid profile and funduscopy, subsequently the patients were classified in to two group, the diabetic retinopathy and without diabetic retinopathy respectively.Results : From 49 subjects were included and observed in this study, from statistical analysis data found that there are relation between age (p=0,001), smoking habbit (p=0,006), hemoglobin (Hb) (p=0.002), duration of diabetic (p=0,0001) and the RBC count with diabetic retinopathy (p= 0,0001 ). From multivariate analysis we found that RBC range lower than 4,8 billion/mm3 are independent predictor for the incidence of diabetic retinopathy.Conclusion : This study found a significant relation between RBC count and diabetic retinopathy and RBC also can predict the incidence of diabetic retinopathy in patient with diabetes.Keywords : RBC, diabetic retinopathy, diabetes.